Pesniške strategije Viljema Černa - Novak-Popov, Irena (Jezik in slovstvo, 2016)
The article analyses the essential poetic strategies in the poetry of Viljem Černo from Torre Valley in Venetian Slovenia. With the use of the plural form of lyrical voice, the poet allies himself with his people; with apostrophe he summons God and praises his homeland; with anaphora, refrain and syntactic-semantic parallelism he intensifies and unifies the represented universe and creates the rhythm of free verse; and with antithetic composition he confronts destructive forces. Textual genres, forms and modes of expression known from the church service address the taste of local readers, but the poet's Torre Valley dialect is raised to the instrument of complex individual content with metaphoric and metonymic innovations.
Keywords: Černo, Viljem, 1937-; Slovene literature; slovenska književnost; slovenska zamejska književnost; slovenska poezija; narečna poezija; slovenski pesniki; Beneška Slovenija; Slavia Friulana; Terska dolina